Demostraciones públicas del sufrimiento privado: Utilidades colectivas de la escritura del trauma - Patricia San José Rico (e-cadernos ces)
Suffering is perhaps one of the most private yet most shared experiences that exists. It is common for individuals as well as whole communities to feel compelled to express their pain by recounting it to others. In fact, when an entire group has been subjected to an ordeal, the need for verbalization is joined with other sociological imperatives such as the self-imposed obligation to give testimony on the behalf of those who cannot, the need to evoke empathy, or even the intent to promote a greater sense of collectiveness amongst the survivors. Using literary as well as autobiographical narratives of trauma, and the opinions of experts, this article demonstrates how trauma writing of the individual, but more specifically of the collective, can be employed for socio-political, cultural and psychological purposes in order to extract collective utility from individual verbalization.